Developing with ring 14 syndrome: A survey in different countries. (November 2014) - Zampini, Laura; Zanchi, Paola; D'odorico, Laura
Abstract This study aimed to assess the communicative skills of children and young adults with ring 14 syndrome and linear 14q deletions, investigating the relationships among their language development and their genetic, clinical, psychomotor and behavioural characteristics. Participants were 36 individuals with chromosome 14 aberrations whose parents completed a questionnaire, specifically developed in five languages, to assess their son's/daughter's development. Data analysis showed that chronological age does not account for the high individual variability found in the participants' skills. The comparison between participants with ring 14 syndrome and participants with 14q linear deletions showed that the former were characterised by a higher occurrence of epilepsy, abnormalities of the retina and autism. The participants with smaller amounts of deleted genetic material were those who had a higher level of language development. Because ring 14 syndrome is a rare genetic disease, the collection of data from a large group of individuals could be helpful to create expectations about the possible developmental outcomes of these children.